Effect of Fresh Banana Plant Waste and its Silage on Dry Matter Intake, Nutrient Digestibility and Rumen Parameters in Osmanabadi Kids - Patil, Shivaram N.; Thirumalesh, T.; Ramachandra, B.; Appannavar, M M; Hiremath, Siddhalinga Swamy; Suranagi, M. D. (Indian Journal of Animal Nutrition, 2019)
Banana plant waste silage was fed to one of the three treatment groups (T3) comprised five kids in each and compared with groups fed fresh banana plant waste (T2) Â and sorghum straw (T1) as source of roughage with concentrate mixture. The silage had pH of 5.05 and DM and CP (%) content of fresh banana plat waste (FBPW) and it silage (FBPWS) was 8.60 and 8.84; 29.97 and 5.44 respectively. The DMI in T2 (0.54%) and T3 (0.98%) groups was significantly (P<0.01) lower than T1 group (1.57%). The daily gain (g/d) of 2.33 and 14.14 in T2 and T3 groups indicated that these were maintenance type of roughage with little supplementation. There was no significant difference between treatments in any of the nutrient digestibility. The DCP and TDN content (%) in T1 and T2 and T3 groups were 4.43 and 66.24; 9.96 and 73.50; 6.21 and 69.55 respectively. The pH values of rumen fluid of the kids were within the normal range in all groups recorded at initial and final of the experiment where as significant difference was observed in TVFA levels between the treatment groups. No significant difference was seen in total nitrogen, TCA precipitable and soluble nitrogen between the treatment groups. It can be concluded that FBPW and its silage could not support even for maintenance level of requirement as a sole source of roughage, which require supplementation of either good quality hay or straw with little CFM.